The Gut-Kidney Axis in Type 2 Diabetes: A Comprehensive Microbiological Perspective on Pathogenesis and Novel Therapeutic Avenues - Aljohani, Najat; Ahmed Aljohani; Nabil Abdullah Yahya Alamir; Mohammed Hussain Ali Al jarah; Kamal Ahmed Aljohani; Hamood Mohammed Hassan (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The human gut microbiome is a dynamic ecosystem, playing a central role in host metabolism. In Type 2 Diabetes, gut dysbiosis-characterized by a reduction in microbial diversity and function-is now considered not only a consequence but also a major contributor to the development of complications such as Diabetic Kidney Disease. Indeed, the gut-kidney axis represents a key route through which microbial metabolites affect renal health. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The aim of this review is to collate recent evidence (2015-2025) on the mechanisms through which gut dysbiosis drives DKD pathogenesis and to assess novel, microbiome-targeted therapeutic strategies. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Extensive literature review focused on microbial taxonomic and functional shifts in T2D and DKD. Review design uses a microbiological approach to dissect the gut-kidney axis, focusing on specific microbial metabolites and pathways. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Diabetic dysbiosis is characterized by the depletion of saccharolytic, SCFA-producing bacteria and the expansion of proteolytic pathobionts, which produce uremic toxins, such as indoxyl sulfate and TMAO. These metabolites foster renal inflammation, oxidative stress, and fibrosis. Therapeutic approaches using pre/probiotics, FMT, and microbial enzyme inhibitors have shown promising potential for the restoration of microbial ecology and mitigation of renal injury. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The gut-kidney axis requires a deep microbiological understanding for the elaboration of novel biomarkers and ecologically-based interventions, with the aim of reducing the burden of DKD in the T2D population.